Opportunities and Barriers in the Partnership Between Foster Families and Schools - Kocsis, Nóra (Central European Journal of Educational Research, 2025)
The primary socialisation area is the family, and the secondary socialisation area is educational institutions. From the point of view of educational sociology, the meeting between the family and the school institution represents the intersection of these socialisation areas (Kozma, 2001; cited in Bacskai, 2020). This issue and its methodological development is something that Joyce Epstein has been working since the 1980s (Epstein, 1986; Epstein, 1987). According to Pusztai (2020a), parenting can be understood as a multifaceted concept, typically referring to the mutual relationship between parent and child. Researchers have focused on this parenting resource mainly from the perspective of the child’s progress at school and learning at home, with the parent acting as an external supporter of the work in school. In this research we focus on the specific characteristics of the cooperation between foster parents and schools, and examine the characteristics of foster parent involvement, along with the supporting and detrimental factors of the partnership between foster parents and teachers at the intersection of child protection and public education. Recently, the number of research studies on foster care has increased (Erdei, 2019; Rácz, 2021), but the relationship between foster parents and teachers is still a little-researched area in Hungary. The novelty of our qualitative research lies in the fact that we are dealing with a special, rarely studied group of parents in Hajdú-Bihar County in terms of family-school relations. The second phase of the analysis has us exploring the narratives of teachers. Our basic research questions are: (1) How can the relationship between foster families and school be characterized? (2) What are the forms of contact and cooperation between foster families and teachers? (3) What factors support or hinder the development of partnerships between foster families and teachers? The focus group data collection was based on semi-structured interview schedules. The research participants were foster parents (N=15) and teachers (N=10). The interviews were coded and analysed using Atlas.ti software. The results show that, overall, there is regular, daily, mainly personal contact between foster parents and teachers. The teacher’s tolerant attitude, taking into account the specific educational situation, appeared as a supportive factor. However, there were also a number of cases reported by foster parents where they had been received negatively by teachers. In order to facilitate collaboration between the two parties, teachers would like to receive training (foster families, foster-parent-school collaboration) and would find it useful to have ongoing supervision.